2010
DOI: 10.1007/s10165-010-0285-7
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression and anxiety in Serbian patients with systemic sclerosis: impact of disease severity and socioeconomic factors

Abstract: This study aimed to assess symptoms of depression and anxiety in Serbian patients with systemic sclerosis (SSc) and to estimate the impact of disease severity and socioeconomic factors on development of depression and anxiety in SSc. Thirty-five patients with SSc and 30 age- and gender-matched healthy individuals participated. Symptoms of depression and anxiety were evaluated using the Beck's depression inventory and Zung's anxiety self-assessment scale. We estimated the impact of gender, age, economic status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Unemployed subjects were more frequent among those with more depressive symptoms; this might support evidence for the role of unemployment as a risk factor for depression, although these patients are also significantly older and therefore might be retired. This finding also suggests that more severe and disabling forms of SSc might lead at the same time to more depression and less ability to work, as also suggested by the multivariate analysis and recent similar contributions on this topic …”
Section: Discussionmentioning
confidence: 59%
“…Unemployed subjects were more frequent among those with more depressive symptoms; this might support evidence for the role of unemployment as a risk factor for depression, although these patients are also significantly older and therefore might be retired. This finding also suggests that more severe and disabling forms of SSc might lead at the same time to more depression and less ability to work, as also suggested by the multivariate analysis and recent similar contributions on this topic …”
Section: Discussionmentioning
confidence: 59%
“…While anxiety has been largely studied in other chronic diseases and in rheumatoid arthritis (RA) [16, 17], only few studies addressed this problem in SSc patients [13, 15, 1820], in which it was associated with education, joint deformity, disease activity, disease duration [21], and gender [19]. However, none of these studies evaluated the potential effects of self-esteem, mouth, and hand disability on anxiety and depression in SSc.…”
Section: Introductionmentioning
confidence: 99%
“…Baubet et al used HADS only as a screening tool for anxiety and depressive disorders in SSc patients then evaluated by Mini International Neuropsychiatric Interview [13]. Nguyen, assessing differences in HADS according to gender, did not evaluate correlation between HADS scores and other parameters [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Around 60% of our SSc patients were depressive and the most common reasons for depression was fatigue and work inhibition. Ostojic et al [37] found that depressive symptoms depended mostly on socioeconomic factors, disease duration, and pain intensity, whereas disease severity had no significant impact on development of depressive symptoms and anxiety. They used BDI to assess depression, their cohort was a little bit larger than ours, and their research was located in Serbia.…”
Section: Discussionmentioning
confidence: 99%